Risk management in Chinese banks during the pandemic of Covid-19 - Yang, Fengmian (2022)
The COVID-19 pandemic posed a huge risk to the world economy, as it caused four meltdowns in the U.S. stock market in March 2020 and contributed to a 4.36% year-over-year reduction in world GDP in 2020. The COVID-19 pandemic was once thought that the pandemic would cause a new financial crisis.